2016
DOI: 10.1016/j.chroma.2016.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution analysis of influenza virus particles using size exclusion chromatography

Abstract: Size exclusion chromatography is a standard method in quality control of biopharmaceutical proteins. In contrast, vaccine analysis is often based on activity assays. The hemagglutination assay is a widely accepted influenza quantification method, providing no insight in the size distribution of virus particles. Capabilities of size exclusion chromatography to complement the hemagglutination assay are investigated. The presented method is comparatively robust regarding different buffer systems, ionic strength a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Therefore, the ability of this new technology chromatography membrane to bind virus at resin capacity at membrane flow rates and using interference multivalent ions was evaluated and exploited for a one-step NDV purification and at constant pH of 8.2. The interference chromatography approach creates interference in the sample (for this study, it the interactions were mainly charge shielding and van der Waals forces, similar to methodologies used previously [52,53] and the equilibration buffer in order to influence separation between biomolecules in the matrix, i.e. product-related and process-related molecules.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, the ability of this new technology chromatography membrane to bind virus at resin capacity at membrane flow rates and using interference multivalent ions was evaluated and exploited for a one-step NDV purification and at constant pH of 8.2. The interference chromatography approach creates interference in the sample (for this study, it the interactions were mainly charge shielding and van der Waals forces, similar to methodologies used previously [52,53] and the equilibration buffer in order to influence separation between biomolecules in the matrix, i.e. product-related and process-related molecules.…”
Section: Discussionmentioning
confidence: 98%
“…This interference method allows for improvements in performance of any chromatographic approach, such as superior resolution, improved binding capacity or augmented flow through productivity. Variations of this technique with anion exchange resins or membranes have been successfully used in the past for virus purification of Influenza H1N1 virus [52] and Influenza A/B virus [53]. One study showed that anions from triprotic kosmostropes, phosphate and citrate, with anion-exchange resins having quaternary amine or primary amine functional groups showed good virus binding, with improved binding by the salt-tolerant primary amine in phosphate buffer at Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the development of SEC technology, commercial analytical columns with pore size of matrix above 100 nm are available now, making it possible to analyze most large virus and VLPs as well as aggregates in the range of 10–100 nm [25]. The TSKgel G6000PWxl column, whose matrix diameter was determined from 20 nm to 2000 nm and the mean value of 250 nm, was reported to separate influenza A virus particle monomers, aggregates and fragments [26].…”
Section: Analytical Techniques For Rapid Characterization and Quantifmentioning
confidence: 99%